The Wayans 4-movie super pack [videorecording (DVD)]. - Wayans, Keenen Ivory; Wayans, Damon; Wayans, Damon; Lawton, J. F. (Jonathan F.); Wayans, Shawn, 1971-; Wayans, Shawn, 1971-; Wayans, Marlon; Wayans, Marlon; McElfresh, Andy; Snowden, Michael Anthony; Cook, Xavier; Grier, David Alan, 1956 June 30-; et al. (Sony Pictures Home Entertainment, 2012)
Blankman: He has no superpowers, no money and no name. He's Blankman, a self-appointed neighborhood crimestopper who's so broke that he fights crime in his underwear.